Analisis Audit Sistem Informasi Menggunakan Framework Cobit 5 Pada E-Learning (Studi Kasus : Universitas XYZ) - Putra Djoelham Sembiring; Boyke Gunawan Manurung; Win Gomgom Parsaulian Sirait (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
In the era of globalization, information technology is growing rapidly in Indonesia. Globalization is a worldwide integration process that encompasses many aspects of life and is characterized by openness, creativity, sophistication, speed, commitment, excellence, strength and free competition. Education as a field of human resource development requires the integration of modern science and technology to transform tacit knowledge gained from direct experience and create explicit knowledge that creates new, sophisticated, and competitive products. As an educational institution, XYZ University has implemented information technology to support academic activities such as e-learning service.